Stress Anisotropy, Long-Term Reservoir Flow Regimes and Production Performance in Tight Gas Reservoirs - Bahrami, H.; Rezaee, M. Reza; Asadi, Mohammad Sadegh (SPE, 2010)
Tight gas reservoirs normally have production problems due to very low matrix permeability and different damagemechanisms during drilling, completion and stimulation. Tight reservoirs need advanced drilling and completion techniques to efficiently connect wellbore to the formation open natural fractures and produce gas at commercial rates. Stress regimes have significant influence on tight gas reservoirs production performance. The stress regimes cause wellbore instability issues while drilling, which can result in large wellbore breakouts. The stress regimes can also control the well long-term production performance, since they affect permeability anisotropy. The preferred horizontal flow direction is expected to be parallel to the maximum in situ horizontal stress. The production and welltest data in non-fractured as well as hydraulically fractured wells in tight reservoirs have indicated the presence of a long-term linear flow regime due to the well and reservoir geometry and also as a result of the permeability anisotropy.The stress anisotropy leads to different permeabilities in different directions, and the natural fractures that are aligned with maximum horizontal stress; they might have larger aperture and greater permeability. Due to the more severe stress anisotropy in tight formations, permeability in maximum stress direction might significantly be larger than permeability in the direction of minimum stress. This study represents evaluation of parameters that might control well productivity and long-term well production performance in tight gas reservoirs. Geomechanical modeling is performed in order to understand the effect of stress anisotropy on aperture evolution of natural fractures in different directions. Furthermore, single well reservoir simulation study is performed in order to generate pressure build-up data for a typical tight gas reservoir, in order to evaluate effect of reservoir geometry and permeability anisotropy on late time linear flow regime, and also assess the well production performance for different well and reservoir conditions.